2010
DOI: 10.1590/s0004-27302010000200022
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of vitamin D3 in non-oily capsules: the role of formulated compounds and implications for intermittent replacement

Abstract: Objective: To evaluate the bioavailability of vitamin D in capsules as compared with oily drops in nuns living in a closed community with very low sun exposure. Methods: A randomized, 2 x 2 crossover, open clinical trial was conducted, with 18 nuns aged between 20 and 75 years. Samples were collected in the fasting state and at 4, 8, 12 and 24 hours following the administration of capsules and oily drops (both containing vitamin D3 66,000 UI plus vitamin A 13,200 UI) to determine serum 25 hydroxivitamin D conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Furthermore, the NLC formulation resulted in more prolonged vitamin D 3 plasma level.Vitamin D is a liposoluble vitamin, and its relative bioavailability could bring about unfavorable conditions. 33 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the NLC formulation resulted in more prolonged vitamin D 3 plasma level.Vitamin D is a liposoluble vitamin, and its relative bioavailability could bring about unfavorable conditions. 33 …”
Section: Resultsmentioning
confidence: 99%
“…In healthy subjects, vitamin D in an oil vehicle produced a greater 25(OH)D response than vitamin D in a powder or an ethanol vehicle [ 43 ]. On the other hand, Coelho et al indicated that vitamin D 3 entering the bloodstream is not affected by capsule formulation [ 44 ]. Since there have been limited studies that have compared the effect of the vehicle substance on vitamin D bioavailability, future studies should examine bioavailability across different vehicle substances, such as oil, lactose powder, and ethanol [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that although limited studies are available, vitamin D in an oil vehicle is more bioavailable than when incorporated in a powder-based vehicle (cellulose or lactose) or in ethanol. However, a recent clinical trial has concluded that vitamin D is more bioavailable from a lactose capsule than from an oily drop formulation (Coelho et al, 2010).…”
Section: Matrix In Which Vitamin D Is Incorporatedmentioning
confidence: 99%